Investigating the Uptake of Hypofractionation for Breast and Prostate Cancer in Sub-Saharan Africa: A Qualitative Study of Physician and Medical Physicist Perspectives - Rohini K. Bhatia, MD; Suzanne M. Grieb, PhD; Katharine A. Rendle, PhD, MPH; Wilfred Ngwa, PhD, MSc; Surbhi Grover, MD, MPH (Advances in Radiation Oncology)
Purpose: In prostate and breast cancer, moderate hypofractionation (HF) has demonstrated comparable, if not greater, efficacy than conventional fractionation. There is a stark disparity in the uptake of HF between North America and Africa. Using the Consolidative Framework for Implementation Research, we evaluated barriers and facilitators for implementing HF in Sub-Saharan Africa (SSA). Methods and Materials: Radiation oncologists and medical physicists working in SSA were recruited via the AORTIC Radiation Oncology Special Interest Group and subsequent snowball sampling. Interviews were conducted virtually between November 2022 and January 2023. Transcripts were analyzed using directed content analysis guided by a Consolidative Framework for Implementation of research interview domains and constructs. Results: In total, 19 interviewees (17 radiation oncologists and 2 medical physicists) from 11 SSA countries participated, of which 94% noted the use of HF (40.05 Gy/15fx or 42.67 Gy/16fx) in breast cancer clinics and 38% in prostate cancer clinics (60-66 Gy/20fx). While nearly all participants identified the benefits of HF for both clinics and patients, many also noted that the lack of long-term data within an African population created discomfort in using HF. Many participants believed in the utility of HF but expressed a lack of confidence in its use caused by uncertainty about the safety of the technique, especially in centers with cobalt or 3-dimensional conformal radiation therapy-only capabilities. In breast HF, participants expressed concern regarding breast size and ideal eligibility criteria for patients. In prostate HF, on-treatment imaging and lack of fiducials were identified as barriers. Key facilitators in adopting HF included hands-on training, partnerships with disease-site-specific individuals with HF experience, and consensus on patient eligibility and technique requirements. Conclusions: HF is regarded as a valuable tool for breast and prostate cancer in SSA, and breast HF is widely used. Attention to the use of 3-dimensional conformal radiation therapy with HF, long-term toxicity data in African populations, and training sessions may facilitate further use of HF for prostate cancer.